Separation of Ti(IV) and Fe(III) from Aqueous Sulphate Solution by Cyanex 272 [Bis(2,4,4-Trimethylpentyl) Phosphinic Acid] in Kerosene: Separation of Ti and Fe from Sulphate Using Cyanex (Biological Sciences - PJSIR, 2009)
Extraction and separation of Ti(IV) and Fe(lll) from aqueous sulphate solution by Cyanex 272 [bis(2,4,4- trimethylpentyl) phosphi nic acid] in kerosene was investigated. Extraction of Ti(IV) and Fe(III) increased with the increase of extractant concentration and decreased with the increase of aqueous phase acidity. About 95% Ti(IV) and 24% Fe(III) was extracted with 0.20 M Cyanex 272 and 0.25 M H S0 . It was thought that Fe(III) was extracted in the 2        4 organic phase by the formation of the species Fe,\ or Fe,\(HA)3 and Ti(IV) as Ti02 .A2 • Data shows that Cyanex 272 can be used as a very effective extractant for Ti(IV) extraction from ilmenite leach solution at high acidity showing large separation coefficient for Ti(IV) from [Ti(IV) and Fe(III)] mixture. The maximum separation factor (P=I 16.50) was obtained at moderate acidity (0.90 MH S0 ) with high extractant (0.20 M Cyanex 272) concentration. The experimen 2        4  tal  data also suggested  that the extraction  of Ti(IV) and Fe(III)  by Cyanex  272 did  not follow simple  extraction mechanism for all the acid ranges. It is likely that solvation mechanism may be operative at high acidity of the aqueous phase.